1998
DOI: 10.1007/pl00006305
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evolution of mariner Elements from Closely Related Species of Fruit Flies (Diptera: Tephritidae)

Abstract: Mariner elements were amplified using the polymerase chain reaction from two species of tephritid flies, Ceratitis rosa and Trirhithrum coffeae. The sequences were approximately 1.3 kb in length. None of these elements appeared to be functional, as in every case the open reading frame (ORF) was disrupted by the presence of frameshifts or stop codons. These elements, Crmar1 and Tcmar1, are very similar to the Ccmar1 element previously amplified from the closely related tephritid species C. capitata and are memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…2003) or population histories remains an open question. The genomes of C. rosa and C. capitata are very similar in size (5.8 × 10 8 and 5.4 × 10 8 bp, respectively; Torti et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2003) or population histories remains an open question. The genomes of C. rosa and C. capitata are very similar in size (5.8 × 10 8 and 5.4 × 10 8 bp, respectively; Torti et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The genome size of C. fasciventris is not yet known but it can be presumed to be within the same size range, considering its high taxonomic affinity to C. rosa (De Meyer 2001a). Moreover, C. rosa is tightly related to C. capitata , sharing a common ancestor about 2 Mya (Torti et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of elements have been reported in a wide variety of organisms ranging from fungi to humans (Langin et al 1995;Augé-Gouillou et al 1995). In dipteran genomes, the MLEs were related to seven major and several minor different mariner subfamilies (Russell and Shukle 1997;Yoshiyama et al 2000;Jacobson et al 1986;Augé-Gouillou et al 1999;Gomulski et al 1997;Torti et al 1998;Ren et al 2006). The majority of MLEs are non-functional, due to multiple inactivating mutations like stop codons, deletions and frame shifts, and the encoded protein is inactive.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have found evidence for horizontal transmission (HT) of MLEs between insect species (Maruyama & Hartl, 1991; Robertson & Lampe, 1995; Brunet et al ., 1999; Gomulski et al ., 2001; Yoshiyama et al ., 2001), but little is known about routes through which this transfer might be mediated, although there is evidence that HT of class II TEs might be mediated through a host‐parasite relationship between arthropod species (P element: Houck et al ., 1991; MLEs: Yoshiyama et al ., 2001). However, the evidence for and against HT remains controversial (Capy et al ., 1994), and most authors have concluded that the evolutionary history of MLEs in vertebrates and invertebrates is characterized by transmission through the host germline and codivergence with host lineages (Torti et al ., 1998; Dharma Prasad et al ., 2002; Casse et al ., 2006; Sinzelle et al ., 2006). In host lineages where MLEs are transmitted vertically, they may be useful as clade markers for their hosts, as has been shown for some class I elements such as SINEs (Cook & Tristem, 1997; Shedlock & Okada, 2000).…”
Section: Introductionmentioning
confidence: 99%